PROBLEMATIKA DAN KEBIJAKAN PEMERINTAH DAERAH TERKAIT KETERSEDIAAN PANGAN DI INDONESIA (STUDI DI SUKA BUMI) - Helmi Helmi; Febri Yanza (Journal of Political Sphere, 2021)
AbstractHumans need food for their survival, both from biological and non-biological natural resources, Indonesia, which is the country with the 4th most populous population in the world, of course has more food needs than countries with a smaller population, If humans only depend on their food needs from nature without managing food, the availability of food in Indonesia is getting thinner day by day even to a critical point. So that the Indonesian government makes the management of food security in this country a priority for its work, the central and regional governments in Indonesia can use technology to process and manage food in Indonesia to strengthen food security, one of which is Sukabumi Regency, how are the problems faced by the government and what are the policies the government to overcome food problems, Through a food production and security approach, the results of this study are the problems that must be faced by regional governments, namely in access to food, problems that arise in the food production process, lack of stability in food availability and lack of quality of food produced. . Policies that can be taken by the Sukabumi regional government to overcome the problem of food availability in this area are improving production and consumption patterns, developing defense technology, and increasing local food security in the Sukabumi Regency area.